Control cultural del Caracol Manzana (pomacea canaliculata) en el cultivo de Arroz bajo riego en el sector de Cedege, cantón Babahoyo - Villacis Gavilanes, Javier Alcívar (2014)
The present investigation work was carried out in Mr. Manuel's lands Villacis located in the area of CEDEGE, Enclosure The Steering wheel to some 15 kms of Babahoyo, with coordinated 68036`22 `` south latitude 97088`51 `` north latitude, height of 14 msnm, precipitation 813 - 334,4 mm, temperature 25,6 - 24,7 0C and heliofanía 76,5 - 34,4. Seed of rice variety Iniap was used 15 obtained of the Agricultural Station Experimental South Coast of National Institute of Investigations, using six treatments, such as: You stake, Channels, Gathering of masses of eggs, adults' Gathering, Combination of stakes and channels and Witness. The design experimental employee trusted totally at random of Blocks with six treatments and four repetitions, tabulating the respective averages with the Test from Tukey to 95% of probability. During the handling of the cultivation all the works agronomic tendientes were executed to obtain a good yield, being: floor analysis, preparation of the floor, siembra, nursery, transplant, siembra distancing, control of overgrowths, control of illnesses, watering, fertilization, harvests.